Terapi Kognitif-Perilakuan Religius untuk Menurunkan Gejala Depresi - Nita Trimulyaningsih; M.A. Subandi (JIP (Jurnal Intervensi Psikologi), 2010)
Depression as the cause of disability has been increasing overtime. It is urgent to find out a form of therapy that accommodates clients faith to enhance the effectiveness of non-religious therapy. The research aims at determining whether Cognitive-Behavioral Religious Therapy (CBRT) was effective to decrease the symptoms of depression. The subject were two women who meet the criteria of moderate and severe depression on Beck Depression Inventory (BDI). Single subject design with ABA design was applied. The visual analysis and clinical significance by practical wisdom were used to see the effectiveness of CBRT. It was concluded that Cognitive-Behavioral Religious Therapy was effective to decrease the symptoms of depression.Key words: Cognitive-Behavioral Religious Therapy (CBRT), depression, faith, Islam.